Representasi Stoikisme Dalam Film ‘The Shawshank Redemption’ : (Analisis Semiotika Ferdinand de Saussure) - Muh. Zaenal Abidin; Abdul Halik; Musi, Suryani (Jurnal Publisitas, 2024)
The purpose of this study is to describe the representation of Stoicism in the film 'The Shawshank Redemption'. This study uses a qualitative approach with a media text analysis method in the form of semiotic analysis of the Ferdinand de Saussure model. The source of this research data is the film 'The Shawshank Redemption' directed by Frank Darabont which has a duration of 142 minutes. The data collection technique uses document analysis and literature study. The data processing and analysis techniques include watching movies (research objects), determining representative scene units to be researched, analyzing Ferdinand de Saussure's markers and signs, interpreting representative scene units, and then drawing conclusions. There are 337 scenes in the film, and 19 relevant scenes were selected. The results of this study show that the representation of stoicism in the film 'The Shawshank Redemption' includes: Self-control (Enkrateia); Accepting things that cannot be changed (amor fati); focus on what can be controlled (the dichotomy of control); humility; and perseverance and endurance.